Georges Florovsky's Monograph Herzen's Philosophy of History: The New Archival Material and the Reconstruction of the Full Text - Gavriljuk, Pavel L. (Harvard theological review, 2015)
Georges Florovsky (1893-1979) was a prominent Russian émigré historian, philosopher, Orthodox theologian, and ecumenist. He was also the first Orthodox theologian to teach at Harvard Divinity School (1957-1964). In the 1920s, Florovsky wrote and defended his dissertation on the leading nineteenth-century Russian public intellectual, Alexander Herzen (1812-1870). Until now, the full text of Florovsky's work had been considered lost. I recently found five documents containing a substantial portion of the dissertation in the Georges Florovsky Papers archive of the St Vladimir's Seminary Library (GFP SVS). This newly discovered material amounts to about one-half of the dissertation and contains some important clues for reconstructing the remaining half of the work. My article discusses: 1) the plan of the dissertation and the history of its composition; 2) Florovsky's defense of the dissertation in Prague in 1923, as summarized in Alexander Izgoev's report, preserved in the Georges Florovsky Papers at the Princeton University Library (GFP PUL); 3) Florovsky's preparation of the dissertation for publication; 4) the description of the newly discovered archival material; and 5) the reconstruction of the dissertation, as preserved in the redactions of 1928-1930. The dissertation is the only monographic study that Florovsky ever finished, his other book-length studies being surveys rather than monographs. The dissertation is also important for understanding the methodological presuppositions of Florovsky's magnum opus, The Ways of Russian Theology (1937).